Role of Thermal Tides and Gravity Waves in Mars Equatorial Mesospheric Cloud Formation Revealed by Mars Climate Sounder Observations. Issue 24 (19th December 2022) - Slipski, M.; Kleinböhl, A.; Kass, D. M.
Abstract: Mesospheric CO2 ‐ice clouds form in one of the coldest regions of Mars's atmosphere, but to date links between the broader thermal structure, dynamical phenomena, and the global and seasonal structure of mesospheric clouds have been tentative due to a limited sample of cloud observations. Combining a comprehensive set of cloud identifications and temperature observations from the Mars Climate Sounder onboard the Mars Reconnaissance Orbiter, we demonstrate for the first time that the spatial distribution and seasonal evolution—including the well‐known yet unexplained solstitial pause—of the aphelion mesospheric cloud population are governed by the interplay of thermal tides and gravity waves. In addition, we present the first investigation of the nighttime cloud distribution and our approach successfully explains the observed day‐to‐night differences. The significant day‐to‐night variability in observed cloud occurrence rates and likelihoods of subcondensation temperatures point toward larger nighttime particle sizes possibly due to more favorable growth conditions. Plain Language Summary: Clouds are common in Mars's atmosphere and some are observed at high altitudes (above 50 km). There is a population of these mesospheric clouds observed during the northern summer season near the equator that are likely composed of CO2 ‐ice. While this region of the atmosphere is often near the frost point, further cooling is needed to enable CO2 ‐ice clouds to form. We have identified thousands of these clouds in Mars Climate Sounder (MCS) observations and used background temperatures derived from MCS to characterize the environment in which these clouds form. We show the distribution of clouds—both spatially and seasonally—is well explained by the complementary effects of thermal tides (global scale oscillations in temperature) and gravity waves (small scale temperature perturbations). Key Points: The combined effects of tides and gravity waves explain the structure of equatorial mesospheric clouds Decreased wave activity drives the solstitial pause in clouds Formation conditions and microphysical properties of clouds differ from day to night